A Framework for Automated Transformation of Legacy SOAP-Based Services to RESTful APIs - Anil Kumar Chitiprolu (International Journal of Engineering, Science and Information Technology, 2026)
Many enterprise information systems continue to rely on legacy Service-Oriented Architecture (SOA) implementations using SOAP-based web services to support critical business operations. Although SOAP provides standardized messaging, strong security, and reliable interoperability, its XML-based communication format and rigid service contracts introduce significant complexity, increase communication overhead, and limit compatibility with modern web and mobile applications. In contrast, RESTful APIs have become the dominant integration paradigm because of their lightweight communication model, scalability, stateless architecture, and native support for JSON-based data exchange. However, replacing legacy SOAP services with newly developed REST APIs is often costly, time-consuming, and disruptive to existing enterprise workflows. This paper proposes an automated middleware framework that transparently transforms legacy SOAP web services into RESTful APIs without modifying existing business logic or backend service implementations. The proposed framework automatically analyzes Web Services Description Language (WSDL) specifications, maps SOAP operations to REST endpoints, and performs bidirectional XML–JSON serialization and deserialization to ensure seamless interoperability between legacy and modern systems. Framework performance is evaluated using three quantitative metrics: the Transformation Efficiency Ratio (TER), measuring transformation correctness; the Payload Reduction Ratio (PRR), measuring communication overhead reduction through JSON serialization; and the Latency Overhead Index (LOI), measuring additional processing delay introduced by the transformation layer. Experimental evaluation was conducted using five representative enterprise SOAP services commonly found in legacy information systems. The proposed framework achieved an average TER of 98.7%, PRR of 63.0%, and LOI of 10.1%, demonstrating high transformation accuracy, substantial payload reduction, and minimal latency overhead. The results indicate that automated middleware-based transformation provides an effective migration strategy for modernizing enterprise integration architectures, enabling organizations to expose lightweight, high-quality RESTful APIs while preserving existing SOAP services, minimizing redevelopment effort, and supporting gradual digital transformation initiatives